A 3D printed PCL/hydrogel construct with zone-specific biochemical composition mimicking that of the meniscus. (16th January 2019) - Bahcecioglu, Gokhan; Hasirci, Nesrin; Bilgen, Bahar; Hasirci, Vasif
Abstract: Engineering the meniscus is challenging due to its bizonal structure; the tissue is cartilaginous at the inner portion and fibrous at the outer portion. Here, we constructed an artificial meniscus mimicking the biochemical organization of the native tissue by 3D printing a meniscus shaped PCL scaffold and then impregnating it with agarose (Ag) and gelatin methacrylate (GelMA) hydrogels in the inner and outer regions, respectively. After incubating the constructs loaded with porcine fibrochondrocytes for 8 weeks, we demonstrated that presence of Ag enhanced glycosaminoglycan (GAG) production by about 4 fold ( p < 0.001), while GelMA enhanced collagen production by about 50 fold ( p < 0.001). In order to mimic the physiological loading environment, meniscus shaped PCL/hydrogel constructs were dynamically stimulated at strain levels gradually increasing from the outer region (2% of initial thickness) towards the inner region (10%). Incorporation of hydrogels protected the cells from the mechanical damage caused by dynamic stress. Dynamic stimulation resulted in increased ratio of collagen type II (COL 2) in the Ag-impregnated inner region (from 50% to 60% of total collagen), and increased ratio of collagen type I (COL 1) in the GelMA-impregnated outer region (from 60% to 70%). We were able to engineer a meniscus, which is cartilage-like at the inner portion and fibrocartilage-like at the outer portion. Our construct has a potential for use as a substitute for total meniscus replacement.